1. The problem statement, all variables and given/known data There is an image but I will reiterate my problem. The writer is solving for t. Okay, easy enough. 2. Relevant equations y-y0 = v0 t + 1/2 a t^2 Textbook says t = sqrt( (2(y-y0) - 2 v0) / a ) 3. The attempt at a solution Shouldn't it be t = sqrt( (2(y-y0) - 2 v0 t) / a ) Let's take it slow. Multiply both sides by two. 2(y-y0) = 2 v0 t + a t^2 Bring (2 v0 t) to left side. 2(y-y0) - 2 v0 t = a t^2 Divide both sides by a. (2(y-y0) - 2 v0 t) / a = t^2 Sqrt both sides. t = sqrt( (2(y-y0) - 2 v0 t) / a ) This really bugs me.